The Arnold Lobel book of Mother Goose - Lobel, Arnold (Knopf, 1997)
An illustrated collection of Mother Goose nursery rhymes, including well-known ones such as "Bah, Bah, Black Sheep" and "Little Boy Blue" and less familiar ones such as "Doctor Foster went to Gloucester" and "When clouds appear like rocks and towers."